2019
DOI: 10.1007/s10803-019-04288-3
|View full text |Cite
|
Sign up to set email alerts
|

Observational and Reported Measures of Language and Pragmatics in Young People with Autism: A Comparison of Respondent Data and Gender Profiles

Abstract: Female children with autism spectrum disorder (FwASD) and performance intelligence quotient (PIQ) over 70 were compared with male children with ASD (MwASD) and typically developing (TD) controls (age 8-11 years) using a range of language and pragmatic measures. Functional ability was assessed using clinical observations and parent, teacher and self-reports. Results were compared between measures, and with direct assessments of language and pragmatics, in order to identify potential biases. This study found tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 49 publications
1
31
0
1
Order By: Relevance
“…Quantitative study analysis helps analyse through data processing approaches using statistical or mathematical methods [14], and the use of quantitative techniques also needs to pay attention to ethics in research analysis so that ethical quality is also maintained [15]. The respondent profile aims to describe the strength of research data that is trusted, accurate, and accountable [16]. Based on the reliability test, it shows if the questionnaire has a consistent quality of questions so that it can become a questionnaire as a measuring tool.…”
Section: Discussionmentioning
confidence: 99%
“…Quantitative study analysis helps analyse through data processing approaches using statistical or mathematical methods [14], and the use of quantitative techniques also needs to pay attention to ethics in research analysis so that ethical quality is also maintained [15]. The respondent profile aims to describe the strength of research data that is trusted, accurate, and accountable [16]. Based on the reliability test, it shows if the questionnaire has a consistent quality of questions so that it can become a questionnaire as a measuring tool.…”
Section: Discussionmentioning
confidence: 99%
“… Sturrock et al (2019b) proposed a battery of direct assessments targeting language (expressive and receptive) at multiple levels (word, sentence and above sentence-level/narrative), word knowledge (semantics), inference and vocabulary of emotion. In subsequent work, the authors proposed a series of functional communication measures ( Sturrock et al, 2019a ) including parent and child questionnaires and observational checklists for social use of language (pragmatic skills). Details of assessment measures are found in Supplementary Appendix 1 .…”
Section: Assessment Of a Subtle Profile Of Difficultiesmentioning
confidence: 99%
“…By contrast, sex/gender differences in pragmatic behaviors during discourse have had more attention in the wider literature. Sturrock et al (2019a) used the Pragmatic Rating Scale (PRS; Landa et al, 1992 ) as a measure of observable pragmatic features within semi-structured discourse (using the Autism Diagnostic Observation Schedule-Second Edition; Lord et al, 2012 ). Total PRS scores ( Sturrock et al, 2019a ) again showed autistic females performing better than autistic males but behind typically-developing females, replicating the pattern found in pragmatic (inference) tasks ( Sturrock et al, 2019b ).…”
Section: Sex/gender Differences In Pragmatics: Inference and Discourse Behaviorsmentioning
confidence: 99%
See 2 more Smart Citations